Livestock grazing regulates ecosystem multifunctionality in semi‐arid grassland. (28th September 2018) - Ren, Haiyan; Eviner, Valerie T.; Gui, Weiyang; Wilson, Gail W. T.; Cobb, Adam B.; Yang, Gaowen; Zhang, Yingjun; Hu, Shuijin; Bai, Yongfei
Abstract: Livestock grazing has been shown to alter the structure and functions of grassland ecosystems. It is well acknowledged that grazing pressure is one of the strongest drivers of ecosystem‐level effects of grazing, but few studies have assessed how grazing pressure impacts grassland biodiversity and ecosystem multifunctionality (EMF). Here, we assessed how different metrics of biodiversity (i.e., plants and soil microbes) and EMF responded to seven different grazing treatments based on an 11‐year field experiment in semi‐arid Inner Mongolian steppe. We found that soil organic carbon, plant‐available nitrogen and plant functional diversity all decreased even at low grazing pressure, while above‐ground primary production and bacterial abundance decreased only at high levels of grazing pressure. Structural equation models revealed that EMF was driven by direct effects of grazing, rather than the effects of grazing on plant or microbial community composition. Grazing effects on plant functional diversity and soil microbial abundance did have moderate effects on EMF, while plant richness did not. Synthesis . Our results showed ecosystem functions differ in their sensitivity to grazing pressure, requiring a low grazing threshold to achieve multiple goals in the Eurasian steppe. Aplain language summary is available for this article. Abstract : Plain Language Summary